PRESENSI DAN PEMINJAMAN BUKU POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG BERBASIS RFID (RADIO FREKUENSI IDENTIFICATION) - Triya Marlina; Dedy Damara; Muhammad Iqbal Nugraha; Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The presence and lending system of books is an important support of information management in the library. The system of presnance, lending, and return of books in polmanbabel library still uses a manual system. This research aims to be able to update the existing manual system in the Polmanbabel Library. RFID is a rapidly evolving technology, RFID technology has been widely used in data information management, one of which is in library information management. The appearance of the system of presence, lending, and return of books is designed using Visual Basic.Net.Visual software Basic.Net is an object-oriented computer programming language. Data collection is done by providing questionnaires to visitors who conduct sample trials from the system created. Based on the results of the test graph proves that the system designed to facilitate the process of Presence, Lending, and Return of books and able to improve service in the Library of Indonesia.